Characterization of the martensitic transformation in the superelastic Ti–24Nb–4Zr–8Sn alloy by in situ synchrotron X-ray diffraction and dynamic mechanical analysis. (15th April 2015) - Yang, Y.; Castany, P.; Cornen, M.; Prima, F.; Li, S.J.; Hao, Y.L.; Gloriant, T.
Abstract: In this work, the martensitic transformation occurring in the superelastic Ti–24Nb–4Zr–8Sn alloy was investigated by tensile tests, in situ synchrotron X-ray diffraction (SXRD) and dynamic mechanical analysis (DMA). The SXRD results clearly showed the diffraction peaks related to the α″ and β phases and their evolution, under loading and unloading conditions, have highlighted the reversible stress-induced martensitic (SIM) transformation. Consequently, a three step deformation sequence was established from both SXRD analysis and tensile test characterization. On the other hand, the characteristic temperatures related to the martensitic transformation under different applied stresses have been determined from the storage modulus and the damping curves by DMA analysis. Very good accordance concerning the critical stress inducing the martensitic transformation was obtained by comparing the results obtained from SXRD, DMA and tensile tests.